(untitled) (Journal of Engineering, 2010)
The hydrodynamic and thermal boundary layers have great effect on the fluid flow and heat transfer between rotating turbine blade. In the present work, the flow and heat transfer is analyzed numerically by solving two dimensional incompressible boundary layer equations. A ( k – ε ) turbulence modeling is used to obtain the eddy viscosity. The finite volume method is introduced to carryout all computational solution with staggered grid arrangement. Due to complex physical domain the original coordinate system is transferred to non orthogonal coordinate system. The calculation of present work done for rotating two dimensional turbine cascade with different rotating speeds (1500 rad/s, 1800 rad/s, 1900 rad/s), and for different Reynolds number (5000, 10000, 100000), in subsonic flow (M<1). The two dimension fluid flow is described by presenting plots of vector and contour mapping for the velocity; pressure and heat transfer fields as well as Nusselt number variation. The results were verified through a comparison with published duct results, good agreement was obtained. The final results were then compared with published results for turbine blades and good agreement was also obtained, the overall comparison show good agreement.